Compostagem de resíduos sólidos domiciliares sob diferentes condições ambientais e de revolvimento - Trevisan, Ismael Carlos (2011)
Composting is a controlled method of treatment for municipal solid waste (MSW), usually operated in uncovered courtyards. In southern Brazil, this condition prolongs the process, requiring more frequent aeration of compost windrows. The objective of this study was to evaluate the composting of MSW conducted in a covered/uncovered environment and with two methods of aeration. The study was conducted in São Domingos do Sul, in 2003/2004. The treatments were: covered windrow with revolving, covered windrow without revolving, uncovered windrow with revolving, and uncovered windrow without revolving. The treatments were arranged in divided plots (windrow with revolving and windrow without revolving) and sub-divided plots (covered and uncovered). It was evaluated as responses the values of temperature, moisture, pH, C, N, C: N, P, K, Ca, and Mg, until the 121th day of composting, which, together with the values of enteropathogenics microorganisms, were compared to the organic compound standards adopted by the Ministry of Agriculture, Livestock and Supply - MAPA. The treatment using covered windrow with revolving provided more days with temperature values corresponding to the thermophile phase (55 to 65 ºC) and with values greater than 65 ºC. The moisture contents in the covered windrows were lesser than those observed for the uncovered windrows, which demanded 20 liters more of water per day, on average. Other advantage of the latter treatment was the non-generation of leachate and the more stable dynamics of the results of pH and C:N relation. In the treatment using covered windrow with revolving the process was completed in 121 days, while for the other treatments the composting had not been completed at this thime. According to the MAPA standards, the treatment using covered windrow with revolving showed no leachate and spreading vectors, being the best treatment in the experiment with the most satisfactory results.